Pengaruh motivasi belajar dan hasil belajar terhadap kemandirian belajar siswa kelas IV SD Negeri Se-Kota Madya Yogyakarta - Safutri, Lhutfia Wahyu; Maulida, Ikrima; Lestari, Eci Anita (Yayasan Mitra Persada Nusantara, 2024)
Learning has an important meaning in the development of human resources. This research aims to determine the influence of social skills and interpersonal intelligence on student learning independence. This research is quantitative research. The sample for this research was 273 students of class IV Intermediate in Yogyakarta City, taken using Stratified Random Sampling. Data collection techniques using observation and psychological scales by designing instruments. The results of the research show that there is a significant influence of learning motivation and interpersonal intelligence on the learning independence of fourth grade students at SD Madya Yogyakarta with a calculated F value of 162.804, and a significant P value of 0.000 <0.05. The R square value is 0.547. This means that social skills (X1) and interpersonal intelligence (X2) simultaneously have a significant effect on learning independence (Y) by 54.7%. In conclusion, learning motivation and interpersonal intelligence have an important role in improving the quality of life of human resources.